Case Report: Various Clinical Manifestations Caused by Varicella-Zoster Virus in a Family - Meng, Qinghong; Wang, Bingsong; Zhang, Xianlai; Li, Zhen; Wang, Wenjie; Yao, Kaihu (Frontiers in Pediatrics, 2022)
A family cluster of varicella-zoster virus (VZV) infections was reported. Four family members (two children and their parents) continuously develop varicella after the grandmother’s herpes zoster. The unvaccinated 16-month-old infant and his mother developed primary varicella with atypical clinical presentation, however, his 28-year-old father presented with a typical generalized vesicular rash. His vaccinated 4-year-old sister was clinically mild, which could be defined as beakthrough varicella case. They infected the same virus strain, but presented various clinical forms.